2022
DOI: 10.1007/s40121-022-00714-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microbiome-Based Therapeutics in Clostridioides difficile Infection: Durable, Long-Term Results of RBX2660

Abstract: A recently published manuscript described findings from a phase 2 open label study of the microbiota-based live biotherapeutic product RBX2660 in patients with two or more previous recurrent Clostridioides difficile infection (rCDI) episodes, and described long-term safety and sustained treatment success through 24 months. As previous studies have typically Infect Dis Ther

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, at 7 and 30 days after treatment, the gut microbiome of the non-responders showed little similarity with the RBX2660 composition. In addition, prior studies showed that patients with recurrent Clostridium difficile successfully treated with RBX2660 at eight weeks had a long-term sustained clinical response with greater than 90% of treatment responders remaining CDI-free at 6, 12, and 24 months [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, at 7 and 30 days after treatment, the gut microbiome of the non-responders showed little similarity with the RBX2660 composition. In addition, prior studies showed that patients with recurrent Clostridium difficile successfully treated with RBX2660 at eight weeks had a long-term sustained clinical response with greater than 90% of treatment responders remaining CDI-free at 6, 12, and 24 months [20].…”
Section: Discussionmentioning
confidence: 99%
“…Results from a phase 3 trial of RBX2660, analyzed with a Bayesian hierarchical model formally incorporating data from a phase 2b trial, showed a treatment success rate of 70.6% ( 68 ). Long-term data (up to 24 months) after treatment with RBX2660 in a phase 2 trial showed durable treatment success, with more than 90% of treatment responders remaining CDI-free at 6, 12, and 24 months ( 69 , 70 ). Microbiota analyses from this phase 2 trial also showed a highly dysbiotic composition before treatment, which converged toward the RBX2660 composition within 7 days after treatment ( 69 , 71 ).…”
Section: Approaches To Restoring the Gut Microbiotamentioning
confidence: 99%
“… 124 Durability of this protective response at 6, 12, and 2 years was demonstrated in a subsequent publication. 125 A phase 2B, placebo-controlled, dose-ranging study followed, showing favorable recurrence rates after a single dose of REBYOTA; in the per-protocol population, 19% (3/24) of participants had recurrence after one dose of drug and one dose of placebo, compared to 52% (13/31) of those who received two doses placebo (p = 0.017). 126 These results culminated in PUNCH CD3, the randomized, double-blind phase 3 trial comparing REBYOTA to placebo that gained FDA approval.…”
Section: Clinical Trials Of the Fda Approved Lbps (Rebyota And Vowst)mentioning
confidence: 99%